2008
DOI: 10.1128/jvi.02188-07
|View full text |Cite
|
Sign up to set email alerts
|

The PDZ Binding Motif of Human Papillomavirus Type 16 E6 Induces PTPN13 Loss, Which Allows Anchorage-Independent Growth and Synergizes with Ras for Invasive Growth

Abstract: The human papillomavirus (HPV) oncogene E6 has been shown to perform multiple functions (p53 degradation, telomerase activation, etc.) that play a role in oncogenic transformation. Beyond known E6 functions, an undefined mechanism that allows cellular invasion requires the E6 PDZ binding motif (PDZBM). Here, we show that HPV type 16 (HPV16) E6 interacts with and induces loss of a protein tyrosine phosphatase (PTPN13) in a PDZBM-dependent manner. PTPN13 loss induced either by the presence of E6 or by a short ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
129
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(135 citation statements)
references
References 43 publications
6
129
0
Order By: Relevance
“…Interestingly, shRNA-induced PTPN13 loss in tonsillar epithelial cells will induce anchorage-independent growth, and PTPN13 loss can also cooperate with activated ras to induce invasive cell growth. Equivalent phenotypes are induced by wildtype, but not PDZ binding-defective, HPV-16 E6 (Spanos et al, 2008b). This provides compelling evidence that the PTPN13 interaction plays a role in HPV-induced malignancy, and it will be interesting to determine how this pathway might impact upon the control of cell polarity.…”
Section: Other Pdz-containing Targets Of E6mentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, shRNA-induced PTPN13 loss in tonsillar epithelial cells will induce anchorage-independent growth, and PTPN13 loss can also cooperate with activated ras to induce invasive cell growth. Equivalent phenotypes are induced by wildtype, but not PDZ binding-defective, HPV-16 E6 (Spanos et al, 2008b). This provides compelling evidence that the PTPN13 interaction plays a role in HPV-induced malignancy, and it will be interesting to determine how this pathway might impact upon the control of cell polarity.…”
Section: Other Pdz-containing Targets Of E6mentioning
confidence: 96%
“…Like MUPP1, PSD95 (Dlg4, another Dlg family member) (Handa et al, 2007) is thought to be a scaffold for signalling complexes, but has so far mainly been described at neuromuscular synapses. The PTPH1/ PTPN3 protein tyrosine kinase (Jing et al, 2007;To¨pffer et al, 2007) and the PTPN13 non-receptor kinase (Spanos et al, 2008b) are also described as HPV E6 targets. Tyrosine kinase phosphorylation is involved in signalling and is commonly altered in transformed cells and cancers.…”
Section: Other Pdz-containing Targets Of E6mentioning
confidence: 99%
“…Degradation of PDZ proteins results in cellular transformation due to loss of cell-cell contact and loss of cell polarity (Storrs and Silverstein, 2007). In addition, it has been demonstrated that the degradation of phosphatase PTPN13 by E6 results in anchorage-independent growth and a Ras-dependent invasive phenotype (Spanos et al, 2008).…”
Section: E6 Proteinmentioning
confidence: 99%
“…HR-HPVE6 proteins also bind to hScrib, a protein involved in epithelial tight junctions, mediating the adhesion of basal cells to the ECM, and at least in some cell types it has been shown that E6 mediates hScrib degradation (Nakagawa & Huibregtse, 2000). Recently, it has been demonstrated that PTPN3, a membrane-bound tyrosine phosphatase that regulates growth factor receptors, is also a PDZ protein that binds and is disrupted by E6 (Jing et al, 2007;Spanos et al, 2008).…”
Section: The Role Of the E6 Proteinmentioning
confidence: 99%
“…Several proteins involved in apoptosis and immune evasion (Bak, FADD,c-Myc, NFX1, procaspase 8, etc) [45,46,47,48] are also targeted by E6 HPV. Bak, a member of the Bcl-2 family, is a proapoptotic protein whose interaction with the viral oncogene leads to the inhibition of apoptosis.…”
Section: E6 Hpvmentioning
confidence: 99%